2005
DOI: 10.1210/jc.2005-0009
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Chain Defects May Present Only with Hypoglycemia

Abstract: Hypoglycemia occasionally results from oxidative phosphorylation deficiency, associated with liver failure. Conversely, in some cases of respiratory chain defect, the impairment in glucose metabolism occurs with normal hepatic function. The mechanism for this hypoglycemia remains poorly understood. We report here three unrelated children with hypoglycemia as the presenting symptom associated with oxidative phosphorylation deficiency but without liver dysfunction. Two patients had, respectively, complex III and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Growth failure presents as short stature in approximately 20% of mitochondrial patients [13], and endocrine problems include hypoparathyroidism, hypothyroidism, diabetes insipidus, diabetes mellitus, hypogonadism, and adrenocorticotropin hormone deficiency [12,17,21]. There are even several case reports of children with mitochondrial disorders with ketotic hypoglycemia as their only presenting sign [4,22]. Although such a presentation is uncommon, children may be dysmorphic, demonstrating features similar to those of fetal alcohol syndrome (microcephaly, round face, high forehead, featureless filtrum, low-set ears, and a short neck) [12].…”
Section: Presentationmentioning
confidence: 99%
“…Growth failure presents as short stature in approximately 20% of mitochondrial patients [13], and endocrine problems include hypoparathyroidism, hypothyroidism, diabetes insipidus, diabetes mellitus, hypogonadism, and adrenocorticotropin hormone deficiency [12,17,21]. There are even several case reports of children with mitochondrial disorders with ketotic hypoglycemia as their only presenting sign [4,22]. Although such a presentation is uncommon, children may be dysmorphic, demonstrating features similar to those of fetal alcohol syndrome (microcephaly, round face, high forehead, featureless filtrum, low-set ears, and a short neck) [12].…”
Section: Presentationmentioning
confidence: 99%
“…Steatosis can lead to impairment of mitochondrial function (18) and ATP production (19). Decreased hepatic glucose production rates as found in inborn errors of metabolism in the oxidative phosphorylation pathway (20) or animal models of shock indicate a close link between mitochondrial dysfunction and impaired gluconeogenesis (21). Finally, signs of hepatic failure have been described in patients with severe malnutrition (22), which would also be associated with decreased EGP.…”
mentioning
confidence: 99%
“…On the other hand, lactic acidosis with an elevated lactate/pyruvate ratio is a hallmark of mitochondrial respiratory chain disorders, which are more common than FBPase deficiency. Mochel et al (2005) reported that hypoglycemic patients with respiratory chain defects and mitochondrial respiratory chain disorders experience a variety of symptoms.…”
Section: Discussionmentioning
confidence: 99%